Preliminary Studies of Left Ventricular Wall Thickness and Mass of Normotensive and Hypertensive Subjects Using M-Mode Echocardiography - Jaafar, M.S. (Penerbit Universiti Sains Malaysia, 2002)
The relationship between left ventricular mass (LVM) and the mean arterial blood pressure (MAP) was investigated, using M-Mode echocardiography. MAP was higher in hypertensive patients (p<0.05, n=9) compared to that of controlled subjects. The results showed that LVM index for hypertensive patients was significantly higher (p<0.05, n=9) than that for the normal group. LVM index correlates fairly (r=0.6) with MAP for hypertensive patients. The results also show that the increase of intraventricular septal wall thickness (IVST) was due to hypertension. The LVM (r =0.9) and IVST (r=0.75) of the normal subjects were linearly dependent on the body surface area (BSA). The hypertensive group revealed a non-linear relationship to the BSA.